Nutritional Methods to Decrease N Losses from Open-Dirt Feedlots in Nebraska - Galen E. Erickson; Terry J. Klopfenstein (The Scientific World Journal)
Nitrogen (N) losses from cattle feedlots are of concern due to loss of valuable N and enrichment of the atmospheric N pool. Nutritional methods to decrease such losses would have economic and environmental benefits. One method to decrease N losses is by increasing carbon (C) on the pen surface. The most cost effective method of decreasing N losses with C may be feeding diets lower in digestibility compared to adding C directly to pens. Therefore, three experiments evaluated feeding corn bran (which is less digestible than corn) as either 0, 15, or 30% of the diet. The 15- and 30%-bran diets increase organic matter (OM) excretion by approximately 0.5 and 1.0 kg per steer per day, respectively. Compared with no bran, feeding 15 and 30% decreased feed efficiency by 7.8 and 10.4%, respectively. Nutrient balance was assessed in two trials from October through May and in one trial from June to September. During the trials from October to May, N losses were decreased by 14.5 and 20.7% for the 15- and 30%-bran diets compared with no bran. Feeding 15 or 30% bran did not influence N losses in the experiment from June to September. Increasing the C:N ratio of manure prior to cleaning open-dirt feedlots had variable results depending on time of year.